Essays in Applied Economics - Wang, Kunyu (Université d'Ottawa / University of Ottawa, 2018)
Chapter 1 ---Does the party of government influence the amount and type of inward foreign investment? The results of a number of correlational studies provide inconsistent evidence. However none of these studies - for any level of government or any jurisdiction - have used methods that allow them to speak to causal effects. Regression discontinuity (RD) method is applied to a set of narrow-margin US gubernatorial elections. Over the course of a four-year term the election of a Republican governor causes a 21% boost in the growth of manufacturing-oriented FDI stock, compared to a Democrat. This effect is robust to a series of challenges. However, the same approach provides no evidence that partisanship matters for the overall level of FDI. Chapter 2 ---Does an economic shock open a window of opportunity for reform, and if it does, how does the institution of a state play a role? The paper investigates how economic shocks affect the structural reforms in various institutions. This paper addresses this issue by using the exogenous variation in the international price of large commodity goods to generate the exogenous change in national income. The analysis relies on a unique mapping between new annual data from 1962 to 2005 on economic shocks from commodity prices and structural reforms in 111 countries. I find significant heterogeneous effects across sectors in autocratic countries. In autocracies, positive economic shocks promote reforms in real sectors, but deter reforms in financial sectors. However the impact of economic shocks on structural reform in democratic countries is nil. Chapter 3 ---The deregulation of branch banking across the United States substantially increased the availability of credit to existing borrowers and others who has previously been excluded. Exploiting the staggered timing of changes across states for identification it is estimated that deregulation caused a 3.3% increase in rates of suicide and a 4.7% increase in rates of divorce. This is consistent with a large body of evidence linking excess debt to various measures of individual and relationship distress. Results are in most cases statistically significant at levels much higher than 1%, and prove resilient in a battery of robustness checks and falsification exercises.
Keywords: Foreign direct investment; Commodity price shock; Bank deregulation